Battery Internal Temperature Measurement Using LC Resonant Tank for Battery Management Systems - Desmon Simatupang; Abdulraouf Benshatti; Sung-Yeul Park (Batteries, 2023)
This paper suggests an embedded battery impedance measurement based on an Inductor Capacitor (LC) resonant tank to measure the battery’s internal temperature for battery management systems (BMS). The purpose of the BMS is to provide state-of-charge (SoC) balancing and the preheating mechanism at sub-zero temperatures. Battery Impedance Spectroscopy (BIS) for battery internal temperature measurement is achieved by an LC resonant tank connected to the batteries in parallel to induce created resonant current and voltage into the battery. The peaks of the voltage and current waveforms are measured and recorded. Then, the resistance of the battery can be calculated by comparing the peak voltage and current waveforms. Since the resistance of the battery is affected by the battery’s internal temperature, the internal temperature of the battery can be estimated. The benefit of using the LC tank for the battery’s internal temperature is to reduce data processing since no window and Fast Fourier Transform (FFT) is needed for this method. In addition, the proposed method measures the battery’s internal temperature without any internal or external temperature sensor. Power Simulation (PSIM) simulation software is used in this proposed method. Panasonic batteries 18650 and a dSPACE DS1104 are used for the experiment to verify the proposed method. The proposed method shows that the LC resonant tank can measure three batteries B1, B2, and B3 internal resistance with 17.87%, 18.14%, and 17.73% errors compared to the Frequency Response Analyzer (FRA). In addition, the total time needed for balancing is 400 s, and the total energy consumed by the preheating mechanism is 0.214%/°C to preheat the lithium-ion batteries (LIBs) from −5 °C to 10 °C.